2015
DOI: 10.1016/j.ymben.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Engineering validamycin production by tandem deletion of γ-butyrolactone receptor genes in Streptomyces hygroscopicus 5008

Abstract: Paired homologs of γ-butyrolactone (GBL) biosynthesis gene afsA and GBL receptor gene arpA are located at different positions in genome of Streptomyces hygroscopicus 5008. Inactivation of afsA homologs dramatically decreased biosynthesis of validamycin, an important anti-fungal antibiotic and a critical substrate for antidiabetic drug synthesis, and the deletion of arpA homologs increased validamycin production by 26% (ΔshbR1) and 20% (ΔshbR3). By double deletion, the ΔshbR1/R3 mutant showed higher transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 35 publications
0
31
0
2
Order By: Relevance
“…Meanwhile, ethanol or temperature shift in fermentation could increase Val-A production (2,10,14). In latest research, addition of 1,4-butyrolactone could also affect metabolic pathway in S. hygroscopicus 5008 (9). Streptomyces fermentation could be influenced by the medium pH obviously, and the secondary metabolism could also be affected (15).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, ethanol or temperature shift in fermentation could increase Val-A production (2,10,14). In latest research, addition of 1,4-butyrolactone could also affect metabolic pathway in S. hygroscopicus 5008 (9). Streptomyces fermentation could be influenced by the medium pH obviously, and the secondary metabolism could also be affected (15).…”
Section: Resultsmentioning
confidence: 99%
“…Different culture conditions included: (i) Fermentation with ethanol and 1,4-butyrolactone. They were added with a final concentration that can achieve the best production of Val-A as the references mentioned (2,9). The purpose is to study the relationship between the pigment and Val-A productivity when an exogenous stimulant which has been proved to enhance Val-A production is added.…”
Section: Validation Of Spectrophotometry Methods For Rapid Determinatimentioning
confidence: 99%
“…149, 150 Tandem deletion of two GBL receptors in S. hygroscopicus increased validomycin titers and productivity by up to 26% (24 g/L) and 45% (9.7 g/L/day), respectively, which are the highest reported values to date. 151 A few studies have suggested that disruption of GBL receptors may negatively affect antibiotic production, though the lower titers observed may be a result of increased production of other secondary metabolites competing for the same biosynthetic precursors. 148 Although GBL identification is hindered by the fact that they are produced at minute levels and our incomplete knowledge of their biosynthesis, GBL receptors and their homologs can be easily identified by sequence analysis.…”
Section: Strategies For Strain Improvementmentioning
confidence: 99%
“…Nowadays many efforts are made to estimate this potential and to get access to the natural products, the biosynthetic pathways of which are encoded in the genomes of the corresponding Streptomyces strains [13][14][15]. The accumulation of high quality genome sequencing data will strongly contribute to implementation of this task [3,4,[6][7][8][9][10][11].…”
Section: Issn 1993-6842 (On-line); Issn 0233-7657 (Print)mentioning
confidence: 99%